Vascular Mechanisms in CNS Trauma - Lo, Eng H.; Lok, Josephine; Ning, MingMing; Whalen, Michael J. (Springer Series in Translational Stroke Research,, 2014)
Vascular Mechanisms in CNS Trauma focuses on the vascular aspects of brain and spinal cord trauma.  Twenty nine chapters are arranged in three sections-Molecular Mechanisms; Experimental Models and Methods; and Clinical Challenges and Opportunities.  The first section addresses topics in the basic biology of brain and spinal cord trauma, ranging from the pathophysiology of cerebral endothelial cells and gliovascular interactions to the role of stem cells in neurovascular repair. The second section covers experimental methods in rodent and in large animal models of CNS injury, as well as the use of biomaterials and biomarkers in studying the mechanisms of tissue response. The third section deals with clinical issues in the monitoring and treatment of the patient with traumatic injury of the brain and spinal cord. Contributors to the book include an integrated mix of basic scientists and clinicians from diverse institutions. By presenting salient issues in CNS trauma from a vascular perspective, this book should make a unique contribution to the understanding of traumatic brain and spinal cord injury.